Cardiovascular Responses to Unilateral, Bilateral, Upper, and Lower Limbs Resistance Exercise - De Oliveira, Jean L. S.; Lima, Leonardo C. R. [UNESP]; Barreto, Renan V. [UNESP]; Kassiano, Witalo; Neto, José De Oliveira Vilar; Filho, Júlio César Chaves Nunes; Banja, Túlio; De Matos, Robson Salviano; Assumpção, Cláudio De O. (My University, 2023)
The effects of different resistance exercises on cardiovascular responses remain elusive. Therefore, the present study aimed to investigate acute cardiovascular responses to unilateral and bilateral upper and lower limb resistance exercise. Young healthy males (n = 22; 26.9 ± 5.4 years, 170.0 ± 6.0 cm, 77.0 ± 10.8 kg) participated in the present study. Four experimental sessions were carried out, each consisting of one of the four exercises: unilateral and bilateral knee extension, unilateral and bilateral biceps curl. Cardiovascular responses (heart rate; HR, systolic blood pressure; SBP, and rate-pressure product; RPP) were measured at rest and after each of the three sets in each resistance exercise. All sets were performed until concentric muscle failure with a rest interval of two min. The HR, SBP, and RPP progressively increased during all sessions with uni-and bilateral exercises of the lower and upper limbs. Importantly, bilateral exercises, mainly of the lower limbs, induced greater increases in HR, and RPP than unilateral exercises of the upper and lower limbs. Regarding SBP, bilateral knee extension exercise induced greater increases than unilateral biceps curl. From a practical standpoint, exercise professionals may consider prescribing unilateral upper and lower limb exercises to alleviate cardiovascular stress, because even when performed until concentric muscle failure, this exercise mode seems to induce lower cardiovascular demand during the resistance training session.
Keywords: blood pressure; hemodynamic responses; rate-pressure product; Strength training